Magnetic Field‐Induced Synthesis of One‐Dimensional Nickel Nanowires for Enhanced Microwave Absorption - Yong Qian; Xiangfu Meng; Hongji Liu; Xingyu Wang; Yefeng Lin; Xinyi Shi; Zhigao Sheng; Hui Wang (Advanced Materials Interfaces, 2023)
Abstract One‐dimensional magnetic nanowires have become one of the ideal candidates for microwave absorption (MA) due to their excellent mechanical properties, large aspect ratio, and excellent electron transport properties. Here, we introduce the synthesis of polyvinylpyrrolidone (PVP)‐directed nickel nanowires (PNNWs) by an externally magnetically induced solvothermal method, and the morphology and properties of PNNWs exhibit a magnetic field‐strength‐dependent relationship. The 9T‐PNNW synthesized at 9 T magnetic field has the characteristics of high aspect ratio, large specific surface area, and good magnetic properties, which endow it with excellent MA performance. The minimum reflection loss (RL) reaches −29.82 dB at 4.08 GHz with the thickness of 4.5 mm and the effective absorption bandwidth (fe) can over 3.6 GHz from 14.4 GHz to 18.0 GHz with a thickness of 1.5 mm. Multiple electromagnetic loss mechanisms are induced to attenuate the electromagnetic wave (EW), in which the dielectric loss dominates, and the magnetic loss, current loss, and resonance effect only play an auxiliary role. This work opens up a new avenue for rational design and preparation of nickel nanowires, and more importantly, the regulation of the magnetic field on the performance of absorbers has reference significance.